Strategi Branding Perusahaan Akurasi.id Dalam Upaya Meningkatkan Iklan Politik - saje, arifin nur (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2024)
Abstract All companies should require branding, including media companies, in order to maintain their sustainability. The right branding strategy needs to be done to strengthen the image of media companies, so as not to lose competitiveness with other companies. So that branding strategy is important for media companies. The purpose of this research is to find out how the branding strategy carried out by the accuracy.id company in an effort to increase political advertising in their company. The method used in this research is qualitative research method, with data collection techniques through 3 methods such as observation, interviews, and documentation, which are carried out directly at the Akurasi.id office. The results of this study based on analysis and field observations, it is found that the accuracy.id branding strategy has several components needed in the study of branding strategies, including brand personality is to increase the value of accuracy.id branding in political value. Brand idendtity by distinguishing the benefits and advantages for politicians so that they will remember the accuracy company as a media for political advertising, and Brand Positioning where the accuracy.id company has placed a position that is effective enough to be recognized as a media that publishes political advertisements. Keywords: branding, branding strategy, political advertising,